Managing Cardiovascular Disease Through a Multidisciplinary Lens: A Literature Review of the Roles of Nursing, Pharmacy, Laboratory Testing, Physiotherapy, Sociology, and Health Administration - Alrabie, Sultan Maniaullah Awad; Alqarni, Meshari Ali Mohammed; Al-Takhim, Mohammed bin Suleiman; Alreshidi, Naif Shamekh Naif; Alzhrani, Abdullah Shalla Rams; Mahnashi, Majed Hussain; Albishi, Ebtsam Saeed Hamed; Jawad, Majed Ahmed Mosa; Jama, Ahmed Ali; Alkhathami, Abdulrahman M. Ali; Alsulami, Saad Dhaifallah Ayash; Sahli, Mohammed Bin Abdulaziz Bin Ahmed (Journal of Posthumanism, 2024)
Cardiovascular disease (CVD) remains the leading global cause of morbidity and mortality. Contemporary evidence indicates that multidisciplinary, team-based models—integrating nursing, pharmacy, laboratory medicine, physiotherapy, sociology, and health administration—improve adherence to guidelines and clinical outcomes across the care continuum while exposing persistent implementation gaps. To critically evaluate and synthesize literature on multidisciplinary CVD management, delineating role-specific contributions, collaborative mechanisms, and system enablers that translate evidence into routine practice. A literature review was conducted using PubMed and Google Scholar (2020–2024). MeSH and free-text terms covered CVD, multidisciplinary/ integrated care, and discipline-specific roles. Eligible peer-reviewed studies (English) included primary research, systematic reviews/meta-analyses, or major guideline statements reporting clinical, behavioral, or organizational outcomes. Nursing interventions consistently improved adherence, risk profiles, and readmission rates. Pharmacist-involved models yielded significant blood pressure reductions, safer pharmacotherapy, and better lipid control, especially under explicit collaborative protocols. Laboratory integration—particularly high-sensitivity troponin pathways and natriuretic peptide use—accelerated accurate diagnosis and informed heart failure management. Physiotherapy via exercise-based cardiac rehabilitation reduced mortality and hospitalizations and improved quality of life through center-based, home-based, and hybrid modalities. Sociological perspectives highlighted social determinants of health; embedding social care enhanced access and adherence. Health-administration-led quality programs and data feedback improved guideline-concordant therapy and reduced readmissions. Key gaps included role clarity, digital workflow integration, scalability, and equity. Multidisciplinary, data-enabled care—anchored by nursing and supported by pharmacy, laboratory medicine, physiotherapy, social care, and administrative QI—improves CVD outcomes. Future work should optimize team composition, communication, and implementation at scale